2018
DOI: 10.1037/str0000084
|View full text |Cite
|
Sign up to set email alerts
|

Traumatization or habituation? A four-wave investigation of exposure to continuous traumatic stress in Israel.

Abstract: Exposure to ongoing violence is a worldwide predicament and may generate different adaptations than those evident in cases of past trauma. Nevertheless, such continuous traumatic stress has only recently begun to attract scientific attention. The present longitudinal study assessed Israeli populations exposed to high and medium intensities of rocket fire in urban and rural communities. Over the course of 4 years, there were 4 assessment points: prior to, proximate to, during, and after a major escalation. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 48 publications
3
28
2
Order By: Relevance
“…Current findings also shed light on the question of reactivity to high‐intensity recurring stressors within a lower‐intensity continuous stressful context. Contrary to some previous studies on a similar population, which suggested that the continuous stressful situation may create habituation and thus less reactivity to specific recurring stressors (Rosenberg, Heimberg, Solomon, & Levin, 2008; Stein, Levin, Gelkopf, Tangir, & Solomon, 2018), current findings show that within such a context, people do continue to react emotionally to specific stressors. Furthermore, it is important to mention that negative emotions under the lower‐intensity condition in the current study (i.e., when there are no sirens) are still more likely to be higher than during routine times, due to reactivity to other war‐related stressors (e.g., damage or fear of damage to self or loved ones, or to property/income) as well as the threat of future sirens, which could go off at any time (see also Greene et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…Current findings also shed light on the question of reactivity to high‐intensity recurring stressors within a lower‐intensity continuous stressful context. Contrary to some previous studies on a similar population, which suggested that the continuous stressful situation may create habituation and thus less reactivity to specific recurring stressors (Rosenberg, Heimberg, Solomon, & Levin, 2008; Stein, Levin, Gelkopf, Tangir, & Solomon, 2018), current findings show that within such a context, people do continue to react emotionally to specific stressors. Furthermore, it is important to mention that negative emotions under the lower‐intensity condition in the current study (i.e., when there are no sirens) are still more likely to be higher than during routine times, due to reactivity to other war‐related stressors (e.g., damage or fear of damage to self or loved ones, or to property/income) as well as the threat of future sirens, which could go off at any time (see also Greene et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the association between trauma exposure and posttraumatic sequalae in the Israeli population is debated: Bleich and colleagues () found that levels of terror‐related trauma exposure and objective threat were unrelated to the risk of PTSD, a finding corroborated in a study conducted by the authors a few years later (Bleich et al., ). These findings might be partially explained by a habituation effect whereby civilians become increasingly accustomed and adjusted to living under continuous threat to life and thus exhibit a decreased risk of developing symptoms of posttraumatic stress (Amir & Sol, ; Stein, Levin, Gelkopf, Tangir, & Solomon, ). Indeed, a habituation effect would be consistent with the finding reported by Shalev, Tuval, Frenkiel‐Fishman, Hadar, and Eth () that the disruption of daily life is more critical in determining PTSD risk than is the direct exposure to terror attacks itself.…”
mentioning
confidence: 99%
“…Native-born Israelis or those who immigrated during their youth may consider themselves to be mentally tough, having grown up in a hostile region while the English speakers may be more willing to reveal vulnerability. Those growing up in Israel may have grown more accustomed to stresses because of wars and terrorist attacks (Stein et al 2018 ). In addition, there is a lack of appropriate use of mental health services in Israel (Elroy et al 2017 ), which may make it be less acceptable for native-born Israelis or those more acculturated to acknowledge and discuss mental health issues.…”
Section: Discussionmentioning
confidence: 99%